ANIMASI, PEMBERDAYAAN DAN PENGUATAN MENGENAI TUGAS POKOK ANGGOTA SEKSI PENDIDIKAN PAROKI DAN DEKENAT SEKEUSKUPAN ATAMBUA - Theodorus Asa Siri; Marianus Sesfao; Wlibrordus C. Usboko (PASCERE: Jurnal Pengabdian kepada Masyarakat, 2026)
Abstract:   Concerns about the quality of education resonate deeply among education advocates. These grievances raise questions about the future of education. In fact, there are still many heart-wrenching issues in education. In this situation, educational reform is necessary. Various projects have been implemented, but the results have not been optimal. The “banking” style of education continues to prevail. When the budget runs out, mentoring activities stopped, as if education were merely about money. This situation causes the Church’s concern, particularly at the parish and deanery levels. Therefore, efforts to revitalize the education section have become a strategic alternative. This is important because members of the Education Section are pioneers in education. The main issues are the suboptimal quality of education and the lack of a robust system to empower human resources. The method involves ongoing animation and empowerment activities. The focus is on the leaders of the parish and deanery education sections. Through these efforts, hopefully a solid and competent education section team will be formed. They will not only be implementers but also innovators to ensure the sustainability of educational programs without relying on funding. In conclusion, improving the quality of education is not a short-term project, but a serious effort to empower and strengthen human resources. The active role of the education sections in parishes and deaneries, education can proceed in a more sustainable, meaningful, and high-quality manner.   Key Words: animation; empowerment; education section. Abstrak: Kecemasan akan kualitas pendidikan menggema dalam sanubari pemerhati Pendidikan. Keluh kesah tersebut menimbulkan pertanyaan tentang masa depan pendidikan. Ternyata. masih banyak persoalan pendidikan menyayat hati. Dalam situasi ini pembaharuan pendidikan diperlukan. Berbagai proyek telah dilaksanakan namun hasilnya belum maksimal. Pendidikan gaya bank terus bergulir. Ketika anggaran habis, kegiatan pendampingan terhenti seolah pendidikan hanya soal uang. Situasi ini menjadi keprihatinan Gereja khususnya di paroki dan dekenat. Maka upaya animasi bagi seksi pendidikan menjadi salah satu alternatif  strategis. Hal ini penting dilakukan karena anggota Seksi Pendidikan merupakan pionir pendidikan. Masalah utama adalah belum optimalnya kualitas pendidikan dan belum adanya sistem yang kuat untuk memberdayakan sumber daya manusia. Metodenya berupa kegiatan animasi dan pemberdayaan berkelanjutan. Fokus kegiatan ditujukan kepada pengurus seksi pendidikan paroki dan dekenat. Melalui upaya ini diharapkan terbentuk tim seksi pendidikan yang solid dan berkompeten. Mereka tidak hanya menjadi pelaksana tetapi juga inovator yang mampu menjaga keberlanjutan program pendidikan tanpa bergantung pada dana semata. Kesimpulannya, peningkatan kualitas Pendidikan bukan proyek jangka pendek, tetapi. upaya serius dalam memperdayakan dan memperkuat sumber daya manusia. Melalui peran aktif seksi pendidikan di paroki dan dekenat, pendidikan dapat berjalan lebih berkelanjutan, bermakna, dan berkualitas. Kata Kunci: animasi; pemberdayaan; penguatan; seksi pendidikan